Teori Perang vs Teori Perang yang Adil: Sebuah Studi Perbandingan - Mas’udi, Syasya Yuania Fadila (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2023)
This study investigates the existence of just war and whether the concept is merely a theoretical construct to satisfy moral principles. Or if it can be applied practically in the ethics of war. While war is always destructive, the just war theory aims to justify it by providing valid reasons for a state to declare war. Using qualitative comparative analysis and a descriptive research approach, the researcher compared the just war theory with the theory of war to determine whether just war exists. The findings indicate that the two theories are fundamentally contradictory, making it impossible for a truly just war. This study sheds light on the ethical complexities of war and contributes to ongoing debates surrounding the justification of military conflict